Policy implementation of child protection in Bandung City, Indonesia - Kartini, Entin; Hermawan, Iwan; Kurniawan, Fajar; Satria, M. Aksal; Permata, Ananda Dwinur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study is intended to explore the implementation of child protection policies in the city of Bandung, which is the main task of the function of a Technical Implementation Unit of the Integrated Service Center for the Empowerment of Women and Children in the City of Bandung. This study uses a qualitative case study approach, primary data obtained from interviews with 8 key informants supported by secondary data derived from observations and supporting documents in the form of policies in child protection that apply in the city of Bandung. The results of the study show that the implementation of child protection policies has not been successful because the service process and the criminal justice system have not been implemented because they are still encountering obstacles. The findings from the results of this study are that services must be implemented and one-stop service is made.